2012
DOI: 10.1097/cej.0b013e32834e3214
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of mammographic density in B-mode ultrasound and real time elastography

Abstract: The aim of our study involved the assessment of B-mode imaging and elastography with regard to their ability to predict mammographic density (MD) without X-rays. Women, who underwent routine mammography, were prospectively examined with additional B-mode ultrasound and elastography. MD was assessed quantitatively with a computer-assisted method (Madena). The B-mode and elastography images were assessed by histograms with equally sized gray-level intervals. Regression models were built and cross validated to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 19 publications
0
19
2
Order By: Relevance
“…Trying to establish measurable phenotypes of breast changes during pregnancy, our group previously developed a surface-based 3D method of measuring the female breast 19 and validated the method in a cohort of pregnant women 20 . Validation of a method of calculating mammographic density using ultrasound 28 in a cohort of pregnant women is still ongoing. There have been a few earlier studies that had similar aims with the technical www.nature.com/scientificreports www.nature.com/scientificreports/ methods that were available in the 1990s 29,30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trying to establish measurable phenotypes of breast changes during pregnancy, our group previously developed a surface-based 3D method of measuring the female breast 19 and validated the method in a cohort of pregnant women 20 . Validation of a method of calculating mammographic density using ultrasound 28 in a cohort of pregnant women is still ongoing. There have been a few earlier studies that had similar aims with the technical www.nature.com/scientificreports www.nature.com/scientificreports/ methods that were available in the 1990s 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…It could be hypothesized that pregnancy in these two groups of women has a different effect on the breast after pregnancy, which has to be further investigated. Moreover, to examine changes of the breast with regard to breast cancer risk and other phenotypes, such as predicted breast density by ultrasound 28 , might be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…It is a single-sided, pulse-echo technique that produces an image of the breast where voxel grey-level is related to the relative acoustic impedance of different tissue types. Although the volume of B-Mode-US may be used to obtain a quantitative measure of a breast lesion, B-Mode US cannot measure an analogous-MD quantity, although it has been shown that B-mode US is able to predict MD measured by mammogram based on the distribution of grey-level values in the US image (R 2 = 0.67 coefficient of determination from ULR analysis) [58]. The same voxel grey-scale analysis has been performed using US elastogram images, but was shown to be less predictive of MD measured by mammogram (R 2 = 0.44 coefficient of determination from ULR analysis) [58].…”
Section: Ultrasound (Us) Based Approachesmentioning
confidence: 99%
“…Different authors have added elastography to Bmode ultrasound evaluation of the breast. It was found that only the grey levels correlated positively with mammographic breast density and the elastographic data [34]. To date, the use of ultrasound in large case-control studies has not been validated as a breast cancer risk predictor.…”
Section: Ultrasoundmentioning
confidence: 99%
“…To date, the use of ultrasound in large case-control studies has not been validated as a breast cancer risk predictor. The use of ultrasound for breast tissue characterisation could be considered in young and pregnant women [34]. Further researches may compare breast percentage density evaluated on ultrasound with the data derived from MRI and DBT.…”
Section: Ultrasoundmentioning
confidence: 99%